Morphological characteristics, extracellular vesicle structure and stem-like specificity of human follicular fluid cell subpopulation during osteodifferentiation - Wiesława Kranc; Mariusz Kaczmarek; Katarzyna Kowalska; Wojciech Pieńkowski; Sylwia Ciesiółka; Aneta Konwerska; Paul Mozdziak; Maciej Brązert; Michal Jeseta; Robert Z. Spaczyński; Leszek Pawelczyk; Bartosz Kempisty (Experimental and Molecular Pathology)
Extracellular vesicles can play an important role in the processes occurring after stem cell transplantation, preventing cell apoptosis, stimulating immunological processes, and promoting the synthesis of extracellular matrix. Human follicular fluid (FF) can be a source of a subpopulation of cells with mesenchymal stem cells (MSCs) properties. Moreover these subpopulations of FF cells can differentiate into osteoblasts. In presented studies flow cytometry of ovarian FF cells confirmed positive expression of MSCs markers such as: CD44, CD90, CD105, CD73 and negative expression of a hematopoietic marker: CD45. The CD90+, CD105+, CD45- cell subpopulation has been obtained during magnetic separation using appropriate antibodies conjugated with microbeads. The extracellular vesicles (EVs) secreted by the cells during osteodifferentiation process differed from those secreted by cells culture in the basal medium. Based on the previous and current electron microscopy research, changes in size, number, and shape would support the notion that released EVs could be crucial to the ovarian FF cell subpopulation differentiation process. Osteogenic differentiation has been confirmed via Alizarin red staining. Therefore, follicular fluid (FF) can be a new source of a cell subpopulation with MSC properties, with the cells capable of differentiating into the osteogenic lineage. EVs could play a key role as mediators in tissue regeneration, especially bone tissue regeneration.